Dissecting the structure-property relationship of ceramic membrane with asymmetric multilayer structures for maximizing permselectivity. (15th July 2022) - Mo, Jiahao; Li, Xianhui; Yang, Zhifeng
Highlights: A model is proposed to dissect the structure-property relation of ceramic membrane. Membrane pore size is mainly dependent on particle size instead of layer thickness. A matching relationship exists between adjacent layers of ceramic membrane. Intermediate layer dominates water permeance of a triple-layer ceramic membrane. The upper-bound tradeoff relation between permeance and selectivity is established. Abstract: Robust ceramic membranes presented attractive features of easy cleaning and excellent stability compared to polymeric membranes. Nevertheless, their inherent relationships between the membrane microstructures and separation properties are not completely clear. In this work, we established a quantitative structure-property model using α -Al2 O3 membrane on account of the theory of filtrated cake to predict the effects of membrane structure-controlled factors ( i.e., α -Al2 O3 particle size and layer thickness) on separation performances ( i.e., solute rejection and water permeance). The simulation results show that membrane pore size mainly depends upon α -Al2 O3 particle size rather than the layer thickness. When the microstructure of top layer in a double-layer asymmetric ceramic membrane is fixed, there exists optimum particle size and layer thickness that constitute the support layer to achieve maximum water permeance. For a triple-layer ceramic membrane, a similar matching relationship exists between top layer and intermediate layer, indicating that the intermediate layer has a vital role in determining water permeance. While the bottom layer has little effect on overall separation property. Finally, the upper-bound tradeoff relationship between permeance and selectivity is further established for the α -Al2 O3 membrane. This study reveals the structure-property relationship of ceramic membrane and provides insights into performance enhancement. Graphical abstract: Image, graphical abstract